2009
DOI: 10.1021/bm901046c
|View full text |Cite
|
Sign up to set email alerts
|

Metastability of Nematic Gels Made of Aqueous Chitin Nanocrystal Dispersions

Abstract: Chitin nanocrystal aqueous dispersions were prepared by acid hydrolysis of crude chitin from crab shells. The resulting dispersions were studied with small deformation oscillatory experiments and polarized optical microscopy under different conditions of nanocrystal concentration, ionic strength, pH, and temperature. The chitin nanocrystal dispersions exhibited a nematic gel-like behavior with increasing solids concentration. The appearance of nematic-like structures could be explained by the Onsager theory fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 40 publications
5
81
0
Order By: Relevance
“…At concentration of 1.00%, it became a self-supporting gel as evidenced by turning the test tube upside-down. These results suggested that the regenerated chitin might be used as a gelling material in a similar way to chitin nanocrystals (Tzoumaki, Moschakis, & Biliaderis, 2010).…”
Section: Resultsmentioning
confidence: 87%
“…At concentration of 1.00%, it became a self-supporting gel as evidenced by turning the test tube upside-down. These results suggested that the regenerated chitin might be used as a gelling material in a similar way to chitin nanocrystals (Tzoumaki, Moschakis, & Biliaderis, 2010).…”
Section: Resultsmentioning
confidence: 87%
“…Chitin nanocrystals (ChN) were produced based on a protocol described by Tzoumaki et al 41 In the original protocol, the crude chitin was rst puried before use. However, EDX analysis (data not shown) showed that the provided crude chitin already had a purity of >98%, and therefore the purication steps were omitted.…”
Section: Formation Of Chitin Nanocrystals (Chn)mentioning
confidence: 99%
“…Here, it can be clearly seen that the chitin aggregates have an average diameter of roughly 100 AE 50 mm. 41 Roughly 3.6 wt% of ChN is required to form a hydrogel. When present in sunower oil in the dilute regime (0.01 wt%), the average size was found to be around 70 mm, similar to the size found with cryo-SEM.…”
Section: Chitin and Chnmentioning
confidence: 99%
See 1 more Smart Citation
“…HCl 3 N 3⋅90 104 30 (Gopalan Nair and Dufresne 2003a;2003b;Gopalan Nair et al, 2003;Lu et al, 2004;Feng et al, 2009;Tzoumaki et al, 2010) 90 104 10 (Nge et al, 2003) 360 120 30 (Hariraksapitak and Supaphol, 2010) Riftia Tubes…”
Section: Crab Shellmentioning
confidence: 99%